Pengaruh Anhidridasetat Terhadap Struktur Molekuler Kayu dalam Stabilisasi Dimensi Kayu Pinus merkusii Et. De Vr. - Sanjaya Sanjaya (Institut Teknologi Bandung, 2001)
Wood is one of several materials that is very useful for man, even wood with less quality tends to be used more. Anthydride-acetic has been used to improve the wood quality by improving the stability of wood dimension. This research studied about the influence of anhydride-acetic on wood molecular structure by studying the change of wood performance, functional group with FTIR method, bound water with DSC method, dimensional stability by determining ASE, and degree of crystallinity with XRD method, on the condition of 110 oC, 15% as long as 24 hours for Pinus merkusii. It is concluded that dimensional stability increase of Pinus merkusii through acetylation, is indicated by the changing of â OH group of wood components with the bigger acetyl group causing amorf region increase. This condition enabled the swelling of wood volume. The substitution of âOH group to a bigger acetyl group caused the steric hindrance which decrease the molecular move of wood component. Therefore, both the swell and the shrink of wood cell walls volume became more difficult, that the swelling of Pinus merkusii volume was smaller or dimensional stability of Pinus merkusii increased.